2012
DOI: 10.1128/iai.06014-11
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Vesicle Release in Bacteria, Eukaryotes, and Archaea: a Conserved yet Underappreciated Aspect of Microbial Life

Abstract: ABSTRACTInteraction of microbes with their environment depends on features of the dynamic microbial surface throughout cell growth and division. Surface modifications, whether used to acquire nutrients, defend against other microbes, or resist the pressures of a host immune system, facilitate adaptation to unique surroundings. The release of bioactive membrane vesicles (MVs) from the cell surface is conserved across microbial life, in bacteria, archaea, fungi, and parasites. MV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
533
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 639 publications
(544 citation statements)
references
References 100 publications
(137 reference statements)
6
533
0
5
Order By: Relevance
“…MVs have also several defensive functions, including a role in antimicrobial peptide resistance (6,10). Reports that membrane vesicles are produced in vivo during infection, that patient sera show reactivity to MV antigens, and that circulating MVs cause sepsis in animal models together support the idea that such vesicles may have a pivotal role in effecting a toxic response in the host, beyond that provided by the infecting microorganism itself (11)(12)(13). In chronic localized infections, such as periodontitis, a common dental disease resulting in irreversible alveolar bone and attachment loss around teeth and eventual tooth loss (14), membrane vesicles may represent an important source of inflammatory stimulants both locally and systemically upon entry into the circulation (15).…”
mentioning
confidence: 79%
“…MVs have also several defensive functions, including a role in antimicrobial peptide resistance (6,10). Reports that membrane vesicles are produced in vivo during infection, that patient sera show reactivity to MV antigens, and that circulating MVs cause sepsis in animal models together support the idea that such vesicles may have a pivotal role in effecting a toxic response in the host, beyond that provided by the infecting microorganism itself (11)(12)(13). In chronic localized infections, such as periodontitis, a common dental disease resulting in irreversible alveolar bone and attachment loss around teeth and eventual tooth loss (14), membrane vesicles may represent an important source of inflammatory stimulants both locally and systemically upon entry into the circulation (15).…”
mentioning
confidence: 79%
“…It has been shown that bacteria, produce EMVs not only in the laboratory but also in biofilms and during infections (Schooling & Beveridge 2006;Deatherage & Cookson 2012). However, until recently the presence of EMVs in natural environments has been largely ignored.…”
Section: Emvs In Bacteriamentioning
confidence: 99%
“…In particular, it has been known for decades that bacteria, including marine species, produce MVs in the laboratory but also in biofilms or during infections (Schooling and Beveridge, 2006;Deatherage and Cookson, 2012). However, until recently, the presence of MVs in natural environments has been largely overlooked by molecular ecologists.…”
mentioning
confidence: 99%
“…The production of extracellular membrane vesicles (hereafter called MVs) is a universal cellular feature, common to the three domains of life (Deatherage and Cookson, 2012). In particular, it has been known for decades that bacteria, including marine species, produce MVs in the laboratory but also in biofilms or during infections (Schooling and Beveridge, 2006;Deatherage and Cookson, 2012).…”
mentioning
confidence: 99%